2017
DOI: 10.1093/jnen/nlx075
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Ultrastructural and Stereological Analyses of Unruptured and Ruptured Saccular Intracranial Aneurysms

Abstract: Insight into processes leading to rupture of intracranial aneurysms (IAs) may identify biomarkers for rupture or lead to management strategies reducing the risk of rupture. We characterized and quantified (ultra)structural differences between unruptured and ruptured aneurysmal walls. Six unruptured and 6 ruptured IA fundi were resected after microsurgical clipping and analyzed by correlative light microscopy for quantitative analysis (proportion of the vessel wall area) and transmission electron microscopy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
11
0
2
Order By: Relevance
“…The first histological alteration of cerebral arteries leading to IA formation is the destruction of the IEL . Although the histological evolution between a healthy cerebral artery to the different steps of IA growth and rupture is not completely known, several studies have shown that the lack of IEL is associated with erosion of luminal endothelium, infiltration of inflammatory cells, loss of SMCs, destruction of the extracellular matrix (ECM), activation of the innate immunity, calcification and/or lipid accumulation . Frösen et al have classified the IA wall in 4 groups using the following parameters: (a) endothelialized wall with linearly organized SMCs; (b) thickened wall with disorganized SMCs; (c) hypocellular wall with either intimal hyperplasia or organizing luminal thrombosis; (d) an extremely thin thrombosis‐lined hypocellular wall.…”
Section: Pathogenesis Of Iasmentioning
confidence: 99%
See 1 more Smart Citation
“…The first histological alteration of cerebral arteries leading to IA formation is the destruction of the IEL . Although the histological evolution between a healthy cerebral artery to the different steps of IA growth and rupture is not completely known, several studies have shown that the lack of IEL is associated with erosion of luminal endothelium, infiltration of inflammatory cells, loss of SMCs, destruction of the extracellular matrix (ECM), activation of the innate immunity, calcification and/or lipid accumulation . Frösen et al have classified the IA wall in 4 groups using the following parameters: (a) endothelialized wall with linearly organized SMCs; (b) thickened wall with disorganized SMCs; (c) hypocellular wall with either intimal hyperplasia or organizing luminal thrombosis; (d) an extremely thin thrombosis‐lined hypocellular wall.…”
Section: Pathogenesis Of Iasmentioning
confidence: 99%
“…27,37,38 Although the histological evolution between a healthy cerebral artery to the different steps of IA growth and rupture is not completely known, several studies have shown that the lack of IEL is associated with erosion of luminal endothelium, infiltration of inflammatory cells, loss of SMCs, destruction of the extracellular matrix (ECM), activation of the innate immunity, calcification and/or lipid accumulation. [39][40][41][42][43][44] Frösen et al 39 have classified the IA wall in 4 groups using the following parameters: (a) endothelialized wall with linearly organized SMCs; (b) thickened wall with disorganized SMCs; (c) hypocellular wall with either intimal hyperplasia or organizing luminal thrombosis; (d) an extremely thin thrombosis-lined hypocellular wall. Based on this classification, it has been shown in Finnish 39 and Swiss 44 cohorts of patients affected by IA that ruptured aneurysmal domes are in vast majority histologically characterized by hypocellular and/or very thin vascular walls and luminal thrombosis (grades c and d).…”
Section: Pathogenesis Of Iasmentioning
confidence: 99%
“…ECs damage is associated with internal elastic lamina pathophysiologic changes and damage, as well as inflammatory cell recruitment, via cytokines and other molecules, and aneurysm wall degeneration or sclerosis. 23,24 Moreover, abnormal collagen fibers in the aneurysm wall indicate a failed wall remodeling. 25 Indeed, differences in wall inflammation and internal elastic lamina were observed between ruptured and unruptured aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…1) According to preceding histological studies on the vascular wall, a cerebral aneurysm may rupture when a thin region of the aneurysm wall becomes unable to sustain the tensile force. 2) A high correlation between the ruptured point of an aneurysm and a thin region of the aneurysm wall 2) and the presence of a thin-walled region in general in most ruptured cerebral aneurysms [3][4][5] have been reported. These studies suggest that thin-walled regions are at high risk of cerebral aneurysm rupture.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that strong inflammation is induced in the wall of cerebral aneurysms that subsequently become thinner and ruptured. [3][4][5] Kataoka et al stated that the influence of blood flow was the cause of this, 3) suggesting the association of blood flow with aneurysm wall thickness reduction. If a hemodynamic characteristic of this process could be clarified, it is highly probable that thin-walled regions can be identified by investigating the characteristic of specific wall areas of interest.…”
Section: Introductionmentioning
confidence: 99%